Reading W.G. Sebald with Alberto Giacometti - Timothy Matthews (Opticon1826, 2006)
Where is Alberto Giacometti? The question seems to arise materially from an engagement with his art and the invitations it seems to extend. Much of his art is a life-long exploration of visual representation itself, of the attempt to visualise objects in a two or threedimensional space; to place people in space. But that placing is elusive, and the places seem to dissolve, making Giacometti’s idiom at once unique and beyond reach, perhaps even untouchable – and this from the creator of such tactile-looking pieces. One way of accepting this invitation to engage with an art that wonders how anything can be engaged with is to ask what it can tell us about the art of others. In this essay, I want to see what the art of Sebald can tell me about the art of Giacometti.